2017
DOI: 10.1007/s11745-017-4269-7
|View full text |Cite
|
Sign up to set email alerts
|

Suksdorfin Promotes Adipocyte Differentiation and Improves Abnormalities in Glucose Metabolism via PPARγ Activation

Abstract: Although the Apiaceae herb family has been traditionally used for the management of type 2 diabetes, its molecular mechanism has not been clarified. Coumarin derivatives, which are abundant in plants of the Apiaceae family, were evaluated for their effects on adipogenesis. We found that suksdorfin significantly promoted adipocyte differentiation and enhanced production of adiponectin, an anti-diabetic adipokine. We also demonstrated that suksdorfin activates peroxisome proliferator-activated receptor gamma (PP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 26 publications
1
5
0
Order By: Relevance
“…Dietary intake of DPCs also led to decreases in the mean size of white adipocytes ( Figure 5). One recent study has reported that dietary intake of suksdorfin, which has a structure similar to that of the DPCs used in this study, induces adipogenesis in WAT in obese, diabetic KK-Ay mice [27]. Thus, these results suggested that the dietary intake of DPCs can induce the conversion of hypertrophic into hyperplastic obesity in HFD-fed mice.…”
Section: Discussionsupporting
confidence: 71%
“…Dietary intake of DPCs also led to decreases in the mean size of white adipocytes ( Figure 5). One recent study has reported that dietary intake of suksdorfin, which has a structure similar to that of the DPCs used in this study, induces adipogenesis in WAT in obese, diabetic KK-Ay mice [27]. Thus, these results suggested that the dietary intake of DPCs can induce the conversion of hypertrophic into hyperplastic obesity in HFD-fed mice.…”
Section: Discussionsupporting
confidence: 71%
“…Regarding the bioactive properties of lovage coumarins, apterin has been previously determined to be a common apiaceous coumarin [ 65 ] and showed antioxidant [ 66 ], anti-tumor [ 67 ], anticholinesterase [ 68 ], antidiabetic [ 69 , 70 ], and anti-inflammatory activities [ 71 ]. Xanthotoxin has demonstrated various bioactivities, such as anticancer, anti-inflammatory, antioxidative stress and antibacterial activities [ 72 ], while pimpinellin was determined to be an effective preventer of platelet-related thromboembolic diseases (such as atherosclerosis [ 73 ]), and isopimpinellin is antibacterial agent against methicillin-resistant Staphylococcus aureus [ 74 ].…”
Section: Resultsmentioning
confidence: 99%
“…PPARα is primarily expressed in the brown adipose tissue and liver, while the expression of PPARγ is abundant in the adipose tissue and works as an important transcription factor in adipocyte differentiation [ 32 ]. Thus, PPARγ agonists have been applied to control insulin resistance induced by obesity [ 33 ]. Moreover, PPARα functions as the physiological stimuli in the fasting state, and it is hypothesized that the free fatty acids transported from adipose tissue to the liver act as ligands and activate PPARα [ 34 ].…”
Section: Discussionmentioning
confidence: 99%